Experimental analysis of a DC current-controlled variable inductor in a DC-DC converter - Mendes, André P.; Baptista, Bruno; Perdigão , Marina S.; Mendes, André M. S. (Neutro à Terra, 2021)
This paper presents an analysis for the experimental set up of a double toroid variable inductor (VI) that is fed by a DC-DC converter. The main objective is to analyze the behaviour of the VI for different power levels, in particular the influence of the control circuit to regulate the inductance of the main winding. By observing the waveform of the main current winding, it is possible to demonstrate the ability to increase or decrease the inductance value. A variable inductor is typically used from linear to saturated state and presents an inversely proportional inductance as a function of the main winding current. By employing this current-controlled double toroid VI it is possible to have both an inductance increase and inductance decrease as a function of the control current by regulating the reluctance of the magnetic cores.